Effects of enalapril in heart failure: a double blind study of effects on exercise performance, renal function, hormones, and metabolic state. Issue 3 (September 1985) - Cleland, J G; Dargie, H J; Ball, S G; Gillen, G; Hodsman, G P; Morton, J J; East, B W; Robertson, I; Ford, I; Robertson, J I
Abstract : Several studies have shown symptomatic and haemodynamic improvement after the introduction of angiotensin converting enzyme inhibitors in patients with heart failure treated with diuretics. The concomitant long term effects of the new orally effective long acting angiotensin converting enzyme inhibitor, enalapril, on symptoms, exercise performance, cardiac function, arrhythmias, hormones, electrolytes, body composition, and renal function have been further assessed in a placebo controlled double blind cross over trial with treatment periods of eight weeks. Twenty patients with New York Heart Association functional class II to IV heart failure who were clinically stable on digoxin and diuretic therapy were studied. Apart from the introduction of enalapril, regular treatment was not changed over the study period; no order or period effects were noted. Enalapril treatment significantly improved functional class, symptom score for breathlessness, and exercise tolerance. Systolic blood pressure was significantly lower on enalapril treatment. Echocardiographic assessment indicated a reduction in left ventricular dimensions and an improvement in systolic time intervals. In response to enalapril, the plasma concentration of angiotensin II was reduced and that of active renin rose; plasma concentrations of aldosterone, vasopressin, and noradrenaline fell. There were significant increases in serum potassium and serum magnesium on enalapril. Glomerular filtration rate measured both by isotopic techniques and by creatinine clearance declined on enalapril while serum urea and creatinine rose and effective renal plasma flow increased. Body weight and total body sodium were unchanged indicating that there was no overall diuresis. There was a statistically insignificant rise in total body potassium, though the increase was related directly to pretreatment plasma renin (r = 0.5). On enalapril the improvement in symptoms, exercise performance, fall in plasma noradrenaline, and rise in serum potassium coincided with a decline in the frequency of ventricular extrasystoles recorded during ambulatory monitoring. Adverse effects were few. In patients with heart failure, enalapril had a beneficial effect on symptoms and functional capacity. The decline in glomerular filtration rate on enalapril may not be beneficial in early heart failure.